2020
DOI: 10.7759/cureus.11629
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the U.S. Childhood Emergency Department Visits for Fall-Related Fractures, 2001–2015

Abstract: The study's objective is to examine national trends in emergency department visits for unintentional fallrelated fractures among children aged 0 to 19 years between 2001 and 2015. Methods The National Electronic Injury Surveillance System-All Injury Program was used to generate national estimates of fall-related fractures treated in emergency departments. Subsequently, according to demographic characteristics, body parts, and sport activities, age-adjusted fracture rates were calculated using the 2000 U.S. pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Additionally, off-balance falls may be more frequent, resulting in young gymnasts reaching out with their arms to brace themselves, which may predispose them to upper extremity injuries. 22 These injuries may be traumatic and require ED presentation, which may further explain their relative rates in these studies as compared with those examining older gymnasts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, off-balance falls may be more frequent, resulting in young gymnasts reaching out with their arms to brace themselves, which may predispose them to upper extremity injuries. 22 These injuries may be traumatic and require ED presentation, which may further explain their relative rates in these studies as compared with those examining older gymnasts.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, off-balance falls may be more frequent, resulting in young gymnasts reaching out with their arms to brace themselves, which may predispose them to upper extremity injuries. 22 These injuries may be traumatic and require ED presentation, which may further explain their relative rates in these studies as compared with those examining older gymnasts. Some studies have reported a sex-specific component to injury location, isolating the most common injury in male gymnasts to be to the upper extremity, particularly the wrist and hand.…”
Section: Discussionmentioning
confidence: 97%
“…Fractures in children are a common presentation to the emergency department, with overall estimated annual incidence rates of 1500-3600 fractures per 100 000 children per year. [1][2][3][4][5] Fractures in childhood cause pain and loss of opportunity. [6][7][8] Most children contained within these series are managed in the community.…”
Section: Introductionmentioning
confidence: 99%
“…However, fracture incidence may be exposed to time trends, as studies from our region have identified higher age- and sex-adjusted hand fracture incidence 1976–1979 than 1950/1955, but similar incidences 1976–1979, 1993–1994, and 2005–2006 [ 5 ]. Studies from many settings report time trends: from Finland with lower pediatric hand fracture incidence in 2005 than in 1983 [ 4 ], from the USA with decreasing fall-related hand/finger fracture incidence between 2001 and 2015 [ 6 ], and from Denmark with lower incidence of metacarpal fractures in age groups 6–11 and 12–15 in 2015–2018 than in 1994–1999 [ 7 ]. Time trends may be different in different regions and during different periods but at least part of the differences may be due to methodological issues, such as different ascertainment methods, or that inferences are based on comparison between absolute incidences or age- and sex-adjusted incidences.…”
Section: Introductionmentioning
confidence: 99%